Comparison of pharmaceutical policies to stimulate use of generics in Japan and Sweden. Issue 2 (June 2016) - Imai, Shinobu; Sundell, Karolina Andersson; Fushimi, Kiyohide
Abstract: Objectives: Among OECD countries, the proportion of total expenditure on health spent on pharmaceuticals is highest in Japan, 20%. In Sweden, the corresponding proportion is 13%. Swedish pharmaceutical expenditures increased dramatically in the 1990s and policy changes were introduced to curb this. Both countries have introduced policy changes to increase cost containment. This study aims to compare the pharmaceutical policies regarding generic medicines in Japan and Sweden. Methods: Information on pharmaceutical policies was collected. We compared pharmaceutical policies according to the 4E (Education, Engineering, Economics, and Enforcement) component framework developed to describe the differences in policies. Results and conclusions: In Sweden, there were several organizational and managerial interventions within the Engineering class. Japan had several positive incentives for health care actors in the Economics category. The Enforcement category had a stronger legal component in Sweden compared to Japan. The Swedish policies were mainly directed towards prescribing and dispensing whereas the Japanese addressed several stakeholders to promote use of generic drugs. The countries were similar with respect to the Education category. Within the Enforcement component the Swedish policies were legally enforced whereas the Japanese to large extent were recommendations. Highlights: Swedish has introduced a number of policy changes and seems to have succeeded to achieve cost-containment of pharmaceutical expenditure whereas the Japanese pharmaceutical policy is under debate. There is still room for improvement of strategy in pharmaceutical policy regarding organizational and managerial interventions in Japan. Sweden had more policies that were legally enforced whereas Japanese policies had the character of promotion of generic drug use.